2019
DOI: 10.1097/pai.0000000000000582
|View full text |Cite
|
Sign up to set email alerts
|

Are Androgen and Estrogen Receptors in DCIS Patients Prognostic Indicators of Relapse Independently of Treatment?

Abstract: Ductal carcinoma in situ (DCIS) is a highly heterogenous tumor that is now more frequently diagnosed because of the increased number of screening programs. Women with DCIS are mainly treated with conservative surgery almost always followed by radiotherapy. Although conventional biomarkers, i.e. ER, PgR, Ki67, and HER2, have been extensively investigated in invasive tumors, little is known about their role in DCIS, especially that of the androgen receptor (AR). In the present study, the expression of convention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…However, there are data about the role of AR/ER ratio as unfavorable prognostic marker only in invasive primary tumor of early BC patients and different cut off values have been used (13,24). Similarly, we previously highlighted the unfavorable prognostic role of the AR/ER ratio in patients with in situ ductal carcinoma, independently of treatment (77,78). About invasive luminal cancers, we found a potential role of AR/PgR ratio > 0.96 in predicting the efficacy of first-line endocrine treatment in HR+ advanced BC (81).…”
Section: The Importance Of the Ratio Between Ar And Other Hormone Rec...supporting
confidence: 62%
See 2 more Smart Citations
“…However, there are data about the role of AR/ER ratio as unfavorable prognostic marker only in invasive primary tumor of early BC patients and different cut off values have been used (13,24). Similarly, we previously highlighted the unfavorable prognostic role of the AR/ER ratio in patients with in situ ductal carcinoma, independently of treatment (77,78). About invasive luminal cancers, we found a potential role of AR/PgR ratio > 0.96 in predicting the efficacy of first-line endocrine treatment in HR+ advanced BC (81).…”
Section: The Importance Of the Ratio Between Ar And Other Hormone Rec...supporting
confidence: 62%
“…It was demonstrated that the AR/ER ratio was statistically higher in relapsed patients of both case series, independently of the treatment, with high AUC values (92% and 80%), in patients treated with surgery and surgery plus radiotherapy, respectively. Taken together these data suggested that the hormone receptor expressions together with AR, could be important prognostic markers able to increase the accuracy in terms of relapse prediction for patients with DCIS ( 77 79 ).…”
Section: Why Studying Armentioning
confidence: 64%
See 1 more Smart Citation
“…Interestingly, TRPM4 is highly expressed in androgen-sensitive prostate cancers required for their aggressive phenotypes [19,20]. Moreover, AR is expressed in all grades of breast DCIS that confers unfavorable prognosis [65][66][67], and TRPM4 was also expressed in all DCIS cases examined in this study. The similarities in the expression profile of TRPM4 and AR in DCIS, breast and prostate cancers suggest a connection of TRPM4 with AR signaling pathway in tumors, and this warrants future investigations.…”
Section: Discussionmentioning
confidence: 61%